Adoption of the 2A Ribosomal Skip Principle to Tobacco Mosaic Virus for Peptide Display - Röder, Juliane; Fischer, Rainer; Commandeur, Ulrich (Frontiers in Plant Science, 2017)
Plant viruses are suitable as building blocks for nanomaterials and nanoparticles because they are easy to modify and can be expressed and purified using plants or heterologous expression systems. Plant virus nanoparticles have been utilized for epitope presentation in vaccines, for drug delivery, as nanospheres and nanowires, and for biomedical imaging applications. Fluorescent protein fusions have been instrumental for the tagging of plant virus particles. The monomeric non-oxygen-dependent fluorescent protein iLOV can be used as an alternative to green fluorescent protein. In this study, the iLOV sequence was genetically fused either directly or via a glycine-serine linker to the C-terminus of the Tobacco mosaic virus (TMV) coat protein (CP) and also carried an N-terminal Foot and-mouth disease virus (FMDV) 2A sequence. Nicotiana benthamiana plants were inoculated with recombinant viral vectors and a systemic infection was achieved. The presence of iLOV fusion proteins and hybrid particles was confirmed by western blot analysis and transmission electron microscopy. Our data suggest that TMV-based vectors are suitable for the production of proteins at least as large as iLOV when combined with the FMDV 2A sequence. This approach allowed the simultaneous production of foreign proteins fused to the CP as well as free CP subunits.